An improved grid integration technique for SPV-based CHB-MLI in distribution network. (17th August 2022) - Kasari, Prabir Ranjan; Bhattacharjee, Subhadeep
The growing power electronics-based nonlinear load increases harmonic contribution in the power system leads to deterioration in the quality of power. The unbalance loading in three phase four wire (3P4W) system allows a neutral current flow, which is an escalating concern for the utility. In this paper, the instantaneous power balance method is employed for solar photovoltaic (SPV)-based nine-level cascaded H-bridge multilevel inverter (CHB-MLI). A modified instantaneous power balance method (PBT) is proposed for integrating SPV-based CHB-MLI with the arrangement specified here as solar photovoltaic shunt active power filter (SPV-SAPF). The zero sequence components have a significant effect on an unbalance 3P4W system, considered as a utility in this paper. FFT analysis done for different voltage levels of CHB-MLI shows that total harmonic distortion (THD) is within a permissible limit. Besides, simulation, experimental results are also provided to validate the performance of the proposed scheme.